Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1021/acs.langmuir.2c00426
|View full text |Cite
|
Sign up to set email alerts
|

Capillary-Driven Ejection of a Droplet from a Micropore into a Channel: A Theoretical Model and a Computational Fluid Dynamics Verification

Abstract: In this work, the problem of re-ejection of a permeating droplet through a membrane pore back to the feed channel when the transmembrane pressure (TMP) becomes zero is investigated. This problem is important in the context of oily water filtration using membranes. In particular, in the novel periodic feed pressure technique (PFPT), which has been proposed to combat membrane fouling, the TMP alternates between the operating value and zero in a periodic manner. During the period in which TMP is high, filtration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In a previous work, Salama et al 39 considered the case of the ejection of a permeating droplet in which two interfaces exist: one in the tube and another one in the reservoir. They showed that when the terminal pressures equalize, the interface inside the tube is able to bring the droplet back to the feed channel, provided the curvature of the interface in the tube is larger than that in the channel.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…In a previous work, Salama et al 39 considered the case of the ejection of a permeating droplet in which two interfaces exist: one in the tube and another one in the reservoir. They showed that when the terminal pressures equalize, the interface inside the tube is able to bring the droplet back to the feed channel, provided the curvature of the interface in the tube is larger than that in the channel.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Furthermore, previous computational fluid dynamics (CFD) investigation shows a slight variation of the axial pressure profiles along the centreline in the reservoir (Salama et al. 2022). More discussion on local entrance losses in such set-ups can be found in several previous works, a good list of which may be found in the work of Waghmare & Mittra (2010).…”
Section: Quasi-one-dimensional Modelling Approachmentioning
confidence: 96%
“…Compared with the pressure loss along the capillary tube length, the local pressure drop at the entrance is expected to comprise only a small fraction (Budaraju et al 2016). Furthermore, previous computational fluid dynamics (CFD) investigation shows a slight variation of the axial pressure profiles along the centreline in the reservoir (Salama et al 2022). More discussion on local entrance losses in such set-ups can be found in several previous works, a good list of which may be found in the work of Waghmare & Mittra (2010).…”
Section: Quasi-one-dimensional Modelling Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea behind the PFPT is to mitigate fouling by preventing the accumulation of oil droplets at the membrane surface during filtration. The fate of an oil droplet during filtration has been comprehensively studied using computational fluid dynamics (CFD) [29][30][31][32][33][34][35] and direct observation over the membrane surface [36] to understand the physics behind the oil settling and clogging of membrane pores. The results showed that an oil droplet, during the filtration process, undergoes either of the following four fates, namely 1) rejection, 2) permeation, 3) pinning, or 4) breakup.…”
Section: Periodic Feed Pressure Techniquementioning
confidence: 99%